Chemical Constituents of the Essential Oils of Aerial Part of the Stachys lavandulifolia Vahl. and Stachys inflata Benth. from Iran - HADI MESHKATALSADAT*, MOHAMMAD; SADEGHI SARABI, REZA; MOHARRAMIPOUR, SAID; AKBARI!, NASSER; PIRAE, MARZIEH (Asian Journal of Chemistry, 2010)
The essential oil of the aerial parts of Stachys lavandulifolia Vahl. (Lamiaceae) and Stachys inflata were isolated by hydrodistillation. The chemical composition of volatile oil was analyzed by capillary GC and GC/MS. The main components were found to be: α-pinene (25.66 %, 2.6 %), myrcene (17.33 %, 2.8 %), β-phellandrene (21.96 %, 0 %), β- caryophylene (14.3 %, 1.78 %), germacrene D (3.91 %, 32.9 %), bicyclogermacrene (1.81%, 7.3 %), respectively.